2011
DOI: 10.2105/ajph.2010.191775
|View full text |Cite
|
Sign up to set email alerts
|

Using a Mixed-Methods Approach to Identify Health Concerns in an African American Community

Abstract: Objectives We used qualitative and quantitative data collection methods to identify the health concerns of African American residents in an urban community and analyzed the extent to which there were consistencies across methods in the concerns identified. Methods We completed 9 focus groups with 51 residents, 27 key informant interviews, and 201 community health surveys with a random sample of community residents to identify the health issues participants considered of greatest importance. We then compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 11 publications
(11 reference statements)
1
39
0
Order By: Relevance
“…Socioeconomic factors (e.g. gender, age, marital status, education, employment and income) were also obtained during the baseline by self-report using items from our previous research [18]. We also used the CDC formula to calculate body mass index (BMI) using self-reported height and weight.…”
Section: Randomization and Interventionmentioning
confidence: 99%
See 4 more Smart Citations
“…Socioeconomic factors (e.g. gender, age, marital status, education, employment and income) were also obtained during the baseline by self-report using items from our previous research [18]. We also used the CDC formula to calculate body mass index (BMI) using self-reported height and weight.…”
Section: Randomization and Interventionmentioning
confidence: 99%
“…Consistent with this approach, we first conducted a multilevel needs assessment with African American residents in the Philadelphia, PA metropolitan area and found that community members were concerned about chronic health conditions such as cardiovascular disease (CVD) and cancer and wanted greater education about obesity reduction and prevention through lifestyle modification and health behavior change [18]. Next, we used developed an integrated approach for providing education about risk factors for chronic diseases to address the priorities identified by community residents as part of a pilot study [20].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations